Avaliação de parâmetros de desempenho de três modelos de biorreatores pneumáticos de bancada - Thomasi, Sérgio Scherrer (2010)
Due to the large number of functional advantages, pneumatic bioreactors have drawn attention in the biotechnology field, being more promising than stirred and aerated tank bioreactors. Parameters such as global gas hold-up (G), volumetric oxygen transfer coefficient (kLa) and average shear rate (Ym) must be considered as performance criteria of these types of bioreactors to provide a better understanding of their hydrodynamics. However, there are no works in literature which compare the performance of bioreactors in terms of shear conditions. Therefore, the aim of the present work was to apply a method proposed in recent literature to evaluate the average shear rate (Ym) in three pneumatic bioreactors of 5-dm3 working volume: bubble column, split airlift and concentric-tube airlift. The volumetric oxygen transfer coefficient (kLa) was chosen as the appropriate characteristic parameter to assess the average shear rate (Ym) in this methodology. Correlations for as a function of superficial gas velocity in the riser region (Ugs) and rheological fluid properties (consistency index, K, and flow index, n) were obtained for each model of pneumatic bioreactor studied. Moreover, correlations between G, Ugs and viscosity (μ) (for Newtonian fluids) and apparent viscosity (μap) (for non-Newtonian fluids) were performed. In general, global gas hold-up (G) was higher for non-Newtonian fluids. The Ym values estimated by the proposed methodology lay within the range of values calculated by classical correlations. The proposed correlations were utilized to predict the Ym during three Streptomyces clavuligerus cultivations carried out at the same specific air flow rate (3.5 vvm) in the different types of pneumatic bioreactors. The lowest values of related to the highest values of Ym consistency index (K) were found for the bubble column bioreactor, and the highest values of related to the lowest values of K were found for the concentric-tube airlift bioreactor. Intermediate values were found for the split airlift bioreactor. The results showed that high Ym values affect the structural health of the mycelia by rupture of the hipha.